2009
DOI: 10.1095/biolreprod.109.077933
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Aquaporins in Sperm Motility Activation of the Teleost Gilthead Sea Bream (Sparus aurata)1

Abstract: The expression of aquaporins in the spermatozoa of the marine teleost gilthead sea bream (Sparus aurata) and their involvement in the motility activation process were investigated. Sperm motility was activated by a hyperosmotic shock, but it was completely inhibited by 10 microM HgCl(2), such inhibition being partially recovered by beta-mercaptoethanol (ME). Conventional RT-PCR using primers specific for S. aurata aquaglyceroporin (glp) and aquaporin 1a (aqp1a) demonstrated the presence of both mRNAs in sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 63 publications
14
55
1
Order By: Relevance
“…On receiving the osmotic signal, ion channels and aquaporins regulate exchange of ions and water through the plasma membrane, respectively, which lead to the initiation of sperm motility [35][36][37]. Zilli et al [37] observed that HgCl 2 at 10 mM completely inhibited sperm activation in gilthead sea bream (Sparus aurata). Their study showed the existence of aquaporins in fish spermatozoa that are detected at the surface of the spermatozoa, both head and flagella.…”
Section: Discussionmentioning
confidence: 99%
“…On receiving the osmotic signal, ion channels and aquaporins regulate exchange of ions and water through the plasma membrane, respectively, which lead to the initiation of sperm motility [35][36][37]. Zilli et al [37] observed that HgCl 2 at 10 mM completely inhibited sperm activation in gilthead sea bream (Sparus aurata). Their study showed the existence of aquaporins in fish spermatozoa that are detected at the surface of the spermatozoa, both head and flagella.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a single study has shown that aquaporin proteins are expressed in the spermatozoa of a marine teleost, the gilthead seabream (Sparus aurata) [7]. This study revealed that the water-specific channel aquaporin-1aa (Aqp1aa) and the glycerol-, urea-, and water-transporting channel Aqp10b are both present in the head and flagellum of ejaculated spermatozoa, and that mercury, an inhibitor of Aqp1aa and -10b water transport [7][8][9][10], blocks sperm motility in seawater [7].…”
Section: Introductionmentioning
confidence: 99%
“…Water may be transported by aquaporins in the plasma membrane (King and Agre, 1996;Verkman, 2002). Sperm of the marine teleost sea bream (Sparus aurata) express aquaporin 1a and aquaglyceroporin, which are localised to the plasma membrane of the head and flagellum (Zilli et al, 2009). In tilapia sperm, it seems reasonable that redoxdependent signal cascades are involved in the regulation of osmotic tolerance and motility.…”
Section: Discussionmentioning
confidence: 99%